Model of Perception of Entrepreneurship: A Reflection on A Mexican Coffee Industry Thorough A Empirical Framework Proposal - Javier CarreÃƒÂ³n-GuillÃƒÂ©n, HÃƒÂ©ctor D. Molina-Ruiz, Arturo SÃƒÂ¡nchez-SÃƒÂ¡nchez, MarÃƒÂa Guada (Social Science Learning Education Journal, 2017)
Community health in contexts affected by floods, fires or frost, coffee marketing provesÂ toÂ be an example to follow to observe the local entrepreneurship.Â In this sense, the objective of this study was to perform a nonÂ -Â experimental, transversal and exploratory study with a nonrandom selection of 300 traderâs coffee.Â From a structural model â Ï2 = 1.335 (5GL) p = 0.935;Â GFI = 0.982;Â AGFI = 0.947;Â RMSEA = 0,000â¡se established reliability (perception scale enterprise with alpha 0.724) and valid for five allusive to perceptions of economic opportunity (32% of the total variance explained), financial (22% of the variance), sales dimensions (16% of the variance), social (10% of the variance) and environmental (3% of the variance).Â the fourth factor reflected the construct (Î² = 0.47), followedÂ byÂ the first (Î² = 0.30) and the fifth factor (Î² = 0.16).Â Based on theoretical and conceptual frameworks the study of entrepreneurial perception vulnerable groups dedicated to the sale of coffee as a way of subsistence is proposed.Â The findings allowÂ toÂ establish a link between the rational choice theory and human capital theory regarding the theory of the commons and the theory of social entrepreneurship as conceptual frameworks to highlight the intervention of Social Work.Keywords Entrepreneurship, finance, sales, social, environment.